The potential / opportunities for leveraging competences: the intangible assets dimension - Eglė Kazlauskienė; Ilona Bartusevičienė; Vilma Tamulienė (Montenegrin Journal of Economics)
A lot of discussions on the variety and identification of individual abilities and / or general competences arise. There is a lack of unanimous approach among scholars. Relevance of the research is proved by numerous publications on human, intellectual, knowledge capital, the impact of intangible assets on economic growth of the country and competitiveness. Some intangible assets could be easily identified, it is easy to determine their value because they are manifested in material forms, e.g. software, and patents; however, there is a increasing demand to identify and evaluate those intangible assets, which are complicated in terms of determining their value; those are e.g. knowledge, experience, abilities, and competences. The aim of this paper is to determine the potential of leveraging abilities to increase income of Lithuanian population by distinguishing abilities in the context of intangible assets definition and evaluation. The methods of research include the following: analysis of scientific literature, comparative analysis, questionnaire survey, summarizing method, statistical data analysis methods. Empirical research allowed determining statistically significant relations between general abilities, population income and expenditure, and education. The majority of surveyed Lithuanian inhabitants think that their income will not change, if they improve their abilities in any of identified domains.